Determination of quality gap for educational services in undergraduate medical education: A cross-sectional study in Saudi Specialized Health Sciences University - Aldarmahi, Ahmed (Saudi Med J, 2019)
OBJECTIVES: To assess the perception and expectation of students about the quality of educational services and identify the gap in educational services. METHODS: This cross-sectional study was conducted at King Saud bin Abdulaziz University for Health Sciences (KSAU-HS) colleges across all regions (Riyadh, Jeddah, and Al-Ahsa) within one academic year (September 2017- April 2018). The difference between the students’ perceptions and expectations was calculated to identify the gap between these 2 opinions. RESULTS: A total of 416 (83.2%) questionnaires were completed with an almost equal ratio of male to female (51% and 49%). There was a significant difference in mean (gap) between students’ expectations and perceptions of educational service quality at KSAU-HS (p<0.05). The results showed negative values for most of the items. It revealed that there is a significant difference between male and female in responsiveness, empathy, and tangible. CONCLUSION: The findings of this study showed that all the dimensions were not up to the expectations of students. The results will help the higher management to initiate a protocol to address all weaknesses.